Red light, green lion - Ryan, Candace; Yerkes, Jennifer (Toronto : Kids Can Press, 2019)
"Inspired by a favourite childhood game (Red Light, Green Light), Red Light, Green Lion is a sweet, sometimes silly, and philosophical picture book that encourages friendship, sharing and literacy. As a green lion stands at a street corner waiting for a green light, a surprising sequence of events takes place. Each page turn brings something new that begins with the letters "li" And while readers may guess, each time, that it will be the expected green light, it usually isn't. First there's the green lion, then a storm, which brings green li--ghtning and rain, a lilac bouquet, a life saver, livestock, library books and lima beans. Eventually after much action and many surprises, the water recedes, the traffic light turns green - green light, finally!"--